Familial Mediterranean fever in Armenian children with inflammatory bowel disease - Amaryan, Gayane; Sarkisian, Tamara; Tadevosyan, Artashes; Braegger, Christian (Frontiers in Pediatrics, 2024)
Inflammatory bowel disease (IBD) and Familial Mediterranean fever (FMF) are inflammatory diseases with complex interactions among genetic, immune, environmental factors.FMF is a monogenic autoinflammatory disease, characterized by recurrent febrile attacks and polyserositis, and is manifested mainly in childhood. FMF is widespread in Armenia. There are reports on the concurrent occurrence of FMF and IBD. MEFV gene mutations may have a diseasemodifying effect on IBD. We have investigated the frequency of MEFV mutations and FMF in Armenian children with IBD and their influence on the clinical course. 69 untreated IBD patients under 18 years were enrolled: 52.1% (36) ulcerative colitis (UC), 21.7% (15) -Crohn's disease (CD), 26.0% (18) -unclassified colitis (IBD-U). The frequency of FMF among them was 36.2% (25/69) and MEFV mutations were identified in 53.6% (37/69). The highest rate of MEFV mutations and FMF was in UC patients (61.1%, 41.6% respectively). 56.7% (21/37) of IBD patients with MEFV mutations had M694V mutated allele, mainly in compound -heterozygous and heterozygous states. There were no associations in the group of IBD patients with coexisting FMF (25) either between any MEFV mutation and type of IBD or coexistence of FMF. 36.0% (9/25) of them developed VEO IBD and carried mainly M694V mutation. We concluded that the carrier frequency of MEFV mutations among Armenian pediatric IBD patients was rather high (53.6%), especially for UC. It is suggested that the MEFV gene is not necessarily a susceptibility gene, but most likely modifies the course of IBD. MEFV genetic testing is recommended for Armenian pediatric IBD patients, especially for VEO UC and IBD-U, atypical IBD course or resistance to the conventional treatment. They should also be asked for isolated febrile attacks, recurrent arthritis, and family history even in the absence of FMF typical symptoms to rule out FMF and its complications.